1979
DOI: 10.3758/bf03329474
|View full text |Cite
|
Sign up to set email alerts
|

Transfer effects in a deductive reasoning problem

Abstract: Transfer in deductive reasoning was investigated through the use of isomorphic matching ("who-done-it") problems. Two groups completed three training problems followed by a test problem. For one group, the same dimensions were used in all training problems; for the other group, new dimensions were used in each training problem. The test problem involved different dimensions from any used in training. Positive transfer was found relative to a notraining control group, but the amount of transfer did not depend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1988
1988

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…First, if the source and target problems share surface and structural features, spontaneous positive transfer should be observed regardless of expertise. In fact, the studies that have shown evidence for spontaneous positive transfer have generally fit into this category (Gick & Holyoak, 1983, Experiment 1; Hayes & Simon, 1977; Holyoak & Koh, 1987; Luger & Bauer, 1978; Ross, 1984; Volbrecht & Schwartz, 1979). Although the subjects in these studies were most likely novices, it seems reasonable to infer that if they showed spontaneous positive transfer under these favorable conditions, experts would have also.…”
Section: Empirical Predictionsmentioning
confidence: 99%
“…First, if the source and target problems share surface and structural features, spontaneous positive transfer should be observed regardless of expertise. In fact, the studies that have shown evidence for spontaneous positive transfer have generally fit into this category (Gick & Holyoak, 1983, Experiment 1; Hayes & Simon, 1977; Holyoak & Koh, 1987; Luger & Bauer, 1978; Ross, 1984; Volbrecht & Schwartz, 1979). Although the subjects in these studies were most likely novices, it seems reasonable to infer that if they showed spontaneous positive transfer under these favorable conditions, experts would have also.…”
Section: Empirical Predictionsmentioning
confidence: 99%